Linking Islamic Religious Ideologies And Sustainable Entrepreneurship - Sufian, Atirah (IJCRT, 2020)
Rapid economic development has resulted in environmental degradation and social conflict in many parts of the world. The never-ending global issues can be controlled if entrepreneurial activities strictly adopt sustainable practices and be more ethical and responsible. Researchers have examined the relationship between religiosity and ethical business decision. However, research on such relationship often produce mix results. Therefore, the purpose of this paper is to assess the potential of religious ideologies in determining ethical decision making of entrepreneurs particularly regarding environmental sustainability. The paper examines sustainability in the light of the Quran and Hadith. It looks at previous research on religiosity and ethics as well as the relationship between religion and awareness towards environmental protection of entrepreneurs. This study introduces a conceptual model that highlights how three religious ideologies in Islam may influence Muslim attitude on environmental sustainability. The paper informs researchers in the area of religion and ethical decision making on the new construct namely religious ideologies as determinants to ethical decision making particularly concerning environmental sustainability.